Analysis of Rainfall Intensity in Madiun Watershed, East Java - Muttaqin, Muttaqin (Forum Geografi, 1997)
The aim of the reasearch in the area of Madiun River Basin is to make and to analyze the Intensity Duration Curve (IDC) i.e. the curve describing graphically the relation between rainfall intensity and rainfall duration in a certain frequent period. Formulation used in the research was Talbot Formula and Ishiguroâs. In the drafting of Intensity Duration Curve it was used specific coefficient i.e by using the rainfall data of fifteen and sixty duration for both applied formulations. The IDC recorded has not mean difference because in both formulation was used coefficient of the same value. The pattern of the rainfall intensity occured directed toward Nort East. It was happened because of the moving clouds directed toward that course. Depression occured at the backward of Mount Lawu, exactly toward East.